2005
DOI: 10.1158/0008-5472.can-05-1572
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Experimental Human Fibrosarcoma Lung Metastasis in Mice by Adenovirus-Mediated Cystatin C Overexpression in the Host

Abstract: Tumor cell invasion and metastasis are associated with degradation of components of the extracellular matrix by different proteinases. Among those, papain-like cysteine proteases, such as cathepsin B, seem to play an important role, as they are associated with poor clinical outcome in different cancers. In this study, we tested whether cystatin C, a natural extracellular inhibitor of papain-like cysteine proteases, can inhibit metastasis when overexpressed at the tumor-host interface. Local overexpression of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 21 publications
3
35
0
1
Order By: Relevance
“…We used lacZ-tagged human fibrosarcoma cells (HT1080lacZ-K15) that typically form large pulmonary metastatic foci and only few single tumor cells as micrometastases, but no macrometastases, in livers (26) to exclude that the TIMP-1 effect was cell type dependent. After challenge of CD1 nu/nu mice with HT1080lacZ-K15, significant reduction of lung metastasis by 93% was observed in TIMP-1-transduced animals compared with mice with virus control (P = 0.018; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used lacZ-tagged human fibrosarcoma cells (HT1080lacZ-K15) that typically form large pulmonary metastatic foci and only few single tumor cells as micrometastases, but no macrometastases, in livers (26) to exclude that the TIMP-1 effect was cell type dependent. After challenge of CD1 nu/nu mice with HT1080lacZ-K15, significant reduction of lung metastasis by 93% was observed in TIMP-1-transduced animals compared with mice with virus control (P = 0.018; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A DNA fragment consisting of Ign-leader sequence and N-TIMP-1 cDNA or full-length human TIMP-1 cDNA (pGEMhTIMP-1; ref. 25), respectively, was obtained and cloned into the adenoviral shuttle plasmid pKA1 (26). Recombinant adenoviruses were generated, purified, and plaque titered as described previously (26).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some types of cancers, the changes in cysteine cathepsin epression or activity have diagnostic or prognostic value with imbalance between cathepsins and cystatins being associated with tumor phenotype. Since the latter ones are able to inhibit cathepsins tumor-associated activity many studies have indicated their potential use in therapeutic approaches (Keppler, 2006;Kopitz et al, 2005;Palermo & Joyce, 2007). Indeed, one of these inhibitors, cystatin C (mostly the one isolated from egg white) has been used in preclinical research studies for more than 20 years, however, it has been introduced into clinical practice quite scarcely.…”
Section: Cystatinsmentioning
confidence: 99%